Possible Mechanisms Underlying the Effects of Glucagon-Like Peptide-1 Receptor Agonist on Cocaine Use Disorder - Zhu, Changliang; Li, Hailiang; Kong, Xuerui; Wang, Yezhong; Sun, Tao; Wang, Feng (Frontiers in Pharmacology, 2022)
Cocaine use disorder (CUD) remains a refractory brain condition characterized by high relapse rate for which there are currently no FDA-approved medications despite decades of research. Since the approval of the first glucagon-like peptide-1 (GLP-1) receptor (GLP-1R) agonist (GLP-1RA) for the treatment of type 2 diabetes and obesity, the potential of GLP-1RAs have been extensively explored and expanded. In this concise review, the biological actions of GLP-1, GLP-1R and GLP-1RA was first introduced. And then, the recent literature examining the actions of GLP-1RA on CUD was reviewed . Finally, the possible pharmacological mechanisms were outlined. A growing body of preclinical evidence reveals that GLP-1RAs appear highly promising in regulating dopamine release and dopamine transporter (DAT) surface expression and DAT function, activating mesolimbic reward system and GABAergic neurons, and ameliorating addiction-like behaviors in animal models of self-administration and conditioned place preference. In addition, the potential effects of GLP-1RA on inhibiting inflammatory cytokines including arachidonic acid was already reported. These research converge to indicate that GLP-1RAs exert a profound influence on the modulation of cocaine-seeking and-taking behaviors likely through multifaceted mechanisms. Although the current preclinical work provides convincing evidence to support GLP-1RA as a promising pharmacotherapy for CUD, other questions such as its clinical availability, impact and the specific mechanisms need to be addressed in future studies.